A Study of Physical Activity Levels and Its Impact on Body Mass Index (BMI) of 8-10 Years Old School Going Children in Mumbai - , Shikha Dwivedi; , Rupali Sengupta (Archives of Current Research International, 2019)
Introduction: Regular physical activity in childhood and adolescence is important for promoting lifelong health and well-being and preventing various health conditions. The 2008, Physical Activity Guidelines for Americans recommended that children and adolescents aged 6 to 17 years should have 60 minutes (1 hour) or more of moderate and vigorous intensity physical activity each day. Unfortunately, many children and adolescents do not meet the recommendations set forth by the guidelines. Aim: To study the physical activity levels and its impact on body mass index (BMI). Methodology: 420 subjects were selected by purposive random sampling method from 5 schools of Mumbai. Physical activity levels of the samples were assessed through the physical activity questionnaire and the height and weight of all the samples were taken to calculate the BMI. Results: It was observed that 39.5% performed sedentary activities for on an average of 0-1 hr/week. Similarly, 74.2% subjects performed moderate to high intensity activities for an average of 0-1 hr/week. Maximum % of subjects (48%) spent 1-2hr/week in performing sedentary activities whereas, when compared to moderate to high intensity activities maximum % of subjects performed only for 0-1 hr/week. Only 116 subjects met the daily requirements of moderate to high intensity physical activity. A total of 33.2% of samples were observed to be under the three categories of wasting (mild, moderate and severe respectively) as per WHO standards.